A SUMMARY OF RESEARCH ON HUMAN AGEING AND LONG LIFE BASED ON PHENOMIC AND GENOMIC DATA - Qudrat Obidjonovich Abduhamidov; Firuza Farxodovna Ibragimova; Gulhon Tagaymurotovna Ishonqulova; Mehri Muratovna Ishanqulova; Nargiza Jabborovna Ahmadaliyeva; Dilfuza Umirzoqova (Web of Journals Publishing, 2025)
Human ageing is a deeply individual process that progresses throughout life and results in significant variation among people in terms of how their physical abilities, health, and lifespan decline. This variation can be seen clearly when comparing healthy and active centenarians to 60-year-olds who are already dealing with multiple chronic illnesses. Molecular research exploring the reasons behind this diversity uses a wide range of methods and targets. In most of these studies, researchers focus on either how long a person lives or on biological markers that show the rate at which ageing occurs in individuals and their tissues.However, unlike many complex age-related diseases, scientists have not yet agreed on a standard set of biomarkers or phenotype definitions that can be used in genetic or genomic research on ageing and lifespan. Similar to what is found in animal studies, common biological features associated with disease risk, healthy ageing, and longevity include immune system and metabolic pathways.Many genomic and epigenomic studies have discovered potentially important genes and biological pathways linked to ageing and lifespan,with APOE and FOXO3A being the most consistently confirmed genetic markers. Research is still ongoing to understand the function of certain genes using cell and animal models. The future of ageing and longevity research depends on better interpretation of genomic data, using computational and systems biology tools, integrating findings from animal models, and ensuring consistency in collecting phenotypic and omics data across long-term and experimental studies.This article is part of a special collection titled Model Systems of Aging, edited by Houtkooper Riekelt.
Keywords: Human Ageing, Phenotypic markers, Functional decline, Dementia, Mendelian diseases, Biological ageing, Epigenetic changes, Biomarkers, Serum proteins and metabolites.